Efeito do guaraná (Paullinia cupana) em parâmetros comportamentais e sistemas purinérgico e colinérgico em modelo de hiperlipidemia - Ruchel, Jader Betsch (2017)
Hyperlipidemia is a condition associated with cognitive and inflammatory disorders, with has a high impact on cardiovascular diseases and central nervous system. Guarana, on the other hand, presents potent anti-inflammatory action and is able to act in the improvement of cogni tion. Thus, this study aimed to evaluate the effect of guarana on behavioral parameters, in purinergic and cholinergic systems of rats with hyperlipidemia. For this, we used adult male Wistar rats previously treated by gavage with guarana 12.5, 25 and 50 mg/kg/day or caffeine (0.2 mg/kg/day) for a period of 30 days. Hyperlipidemia was acutely induced by a single intraperitoneal injection with 500 mg/kg of Poloxamer-407. Simvastatin (0.04 mg/kg) was administered only after induction. Memory tests and anxiety evaluations were performed. The cortex, cerebellum, hippocampus, hypothalamus, and striatum were separated for evaluation of acetylcholinesterase activity. Peripheral blood lymphocytes were separated for the determination of the activity of purinergic enzymes. In addition, serum concentrations of nucleotides and nucleosides, biochemical parameters and inflammatory profile were determined. Our data demonstrate that guarana powder and caffeine were able to prevent elevation of total cholesterol and LDL levels and in aspartate aminotransferase activity caused by hyperlipidemia. These compounds acted to prevent alterations in AChE activity and decreased memory capacity caused by hyperlipidemia in hippocampus. Guarana and caffeine promoted changes in the activity of E-NTPDase and E-ADA enzymes as a compensatory organic response, contributing to the change in inflammatory profile. Guarana and caffeine also acted to prevent elevation of ATP levels and increase extracellular adenosine. In addition, they acted to prevent the increase of INF-γ and potentiated the elevation of IL-4 levels caused by hyperlipidemia, contributing to an anti -inflammatory profile. These results obtained suggest that guarana is a promising compound to be used as an adjuvant therapy to benefit patients with hyperlipidemia and cognitive disorders.